How rational Aminoglycosides are being used in critically ill patients? Results from a teaching hospital in north of Iran - Ebrahim Salehifar; Gohar Eslami; Nematollah Ahangar; Mohammad Reza Rafati; Shafagh Eslami (Babol University of Medical Sciences, 2015)
Background: Resistance to antimicrobial agents including aminoglycosides (AGs) is a great concern that is mainly related to inappropriate use. Since there were not adequate data regarding how rationally AGs are being prescribed in our critically ill patients, this study was conducted to determine the main issues in the area of appropriate use of this antibiotic class.   Methods: One hundred patients who were in the intensive care units (ICUs) of Imam Khomeini Teaching Hospital from February 2012 to August 2012 were included. A data gathering form was prepared based upon the recommendations provided by Up-to-date (20.1) 2012 and Medscape 2013. All demographic characteristics and other information about time of beginning and duration of dosage, interval of administration of AGs and creatinine (Cr) level were collected. In statistical analysis, SPSS Version 16 software was used. Independent samples t-test was used to compare the quantitative and chi-square for qualitative variables.  Results: Sixty six (66%) of patients received gentamicin and 38% received amikacin. In 27% of patients, serum creatinine (Cr) had been checked before and after AGs administration and 4 patients had no renal function monitoring. Monitoring of serum concentration and Cr clearance estimation was not carried out for any patients. Culture and laboratory sensitivity tests were done on 17 patients and E-coli (57%) was the most common isolated organism.  Conclusion: The results of this study revealed that majority of the hospitalized patients in the ICU and the dosage of AGs had not been adjusted to renal function.